2003
DOI: 10.1080/01449290310001624356
|View full text |Cite
|
Sign up to set email alerts
|

Work environment and computer systems development

Abstract: Investigations indicate that different types of work environment problems in computer supported work are constantly increasing. Most efforts to improve the work environment are focused on physical or psychosocial aspects, since these are easier to measure and provide efficient solutions to. Mental workload and cognitive problems are of a more complex nature, and are therefore more seldom studied and solved. Solutions to work environment problems are usually applied to already constructed work situations throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 7 publications
0
24
0
2
Order By: Relevance
“…It is particularly difficult because of human's inability to successfully 'shut down' from mental stress, meaning that these stress levels stay high during breaks [21]. Mental workload and cognitive problems are of a complex nature, more difficult to measure and to provide efficient solutions to, and are more seldom studied or solved in comparison to physical problems in computer-supported work [22]. The realisation of cognitive relaxation during breaks, even though the user has deadlines to meet, presents both possibilities and challenges for future preventive measures.…”
Section: Design Opportunity 1: Aiming For Cognitive Relaxationmentioning
confidence: 99%
“…It is particularly difficult because of human's inability to successfully 'shut down' from mental stress, meaning that these stress levels stay high during breaks [21]. Mental workload and cognitive problems are of a complex nature, more difficult to measure and to provide efficient solutions to, and are more seldom studied or solved in comparison to physical problems in computer-supported work [22]. The realisation of cognitive relaxation during breaks, even though the user has deadlines to meet, presents both possibilities and challenges for future preventive measures.…”
Section: Design Opportunity 1: Aiming For Cognitive Relaxationmentioning
confidence: 99%
“…Traditionally, occupational health experts work in isolation from the software development process. They evaluate and suggest improvements to existing workplaces and tools [3]. It is, however, often too late to do something about poorly designed software tools once they have been installed and are running.…”
Section: Digital Work Environment and Healthy Workmentioning
confidence: 99%
“…This model suggests that the combination of perceived demands and perceived control at work is a determining factor for stress. This model was used since our previous research, see for example [2] and [3] that have shown that the model is easily understood and applied in organisations when the digital work environment has been discusses. The figure below illustrates the Demand-ControlSupport Model.…”
Section: Digital Work Environment and Healthy Workmentioning
confidence: 99%
“…An information system can, for example, enforce adherence to hierarchies and bureaucracy, affect established work procedures and, by extension, the shaping of professional identities in a workforce (see for example [9]). Moreover, as they have increasingly become an intrinsic part of our work environment [10], information systems are likely to cause unhealthy amounts of stress if they do not support us effectively and enable us to work efficiently. Given this relationship between the environment in which information systems are implemented and the work they are designed to enable and support, it is surprising that many organisations still make the mistake of regarding their development and introduction as primarily an IT project, rather than an organisational change project.…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents how students and employees at the university envision their future, taken to mean four years hence, if ideally supported by technology and organisational structures. The method used to produce these visions (the vision seminar process) has previously been used in numerous other contexts, such as health care, industrial process control and train traffic control (see, for example, [10][11]), over a period of more than 20 years. One of the outputs of the vision seminar process is a series of documents containing user stories or "scenarios" told by user representatives from different stakeholders.…”
Section: Introductionmentioning
confidence: 99%